PELATIHAN PENGOLAHAN DAUN MIMBA SEBAGAI PESTISDA PEMBASMI TANAMAN DAN PEMASARAN PADA PRODUK PESTISIDA DAUN MIMBA - Rista, Karolin; Nur Kholis S,, Ahmad; Achmad G, Bintang (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Pest resistance to insecticides is a global phenomenon that is felt by all stakeholders (Stakeholders) especially farmers both in developed countries and in developing countries such as Indonesia. Mimba, Azadirachta indica is one of the effective and relatively safe plant insecticides in the environment. Neem plants contain azadirachtin compounds, salanin, meliantriol, lead, and nimbidine which influence the biological activity of pest insects. Azadirachtin can interfere with insect growth, acting as a decrease in appetite and sterilizers. Salanin works as an appetite-lowering agent and pests meliantriol as a repellent. Some seeds can be used to control whitefly (Bemisia tabaci), armyworm (Spodoptera litura), and pod borer, Maruca testulalis in legumes.